Обґрунтування необхідності запровадження оцінювання фінансових інструментів і технологій - Кузнецова, Світлана Олександрівна; Строков, Євген Михайлович; Кузнецов, Сергій Володимирович (Видавничий дім "Гельветика", 2024)
Стаття присвячена актуальним питанням запровадження оцінювання фінансових інструментів і технологій, що є критично важливим для забезпечення ефективного функціонування фінансового ринку. Метою статті є обґрунтування необхідності запровадження оцінювання фінансових інструментів і технологій для забезпечення економічної стабільності. Окреслено, що це дозволяє інвесторам, компаніям і регуляторам отримувати об'єктивну інформацію про ризики та перспективи інвестицій, що сприяє прийняттю обґрунтованих рішень. Досліджено, що в умовах швидкого розвитку фінансових технологій, оцінювання також допомагає виявити інновації, що можуть підвищити конкурентоспроможність, знизити витрати та підвищити ефективність фінансових процесів. Крім того, це сприяє прозорості ринку, запобіганню шахрайству і фінансовим кризам, забезпечуючи стабільність та розвиток економіки в цілому.

The article is devoted to the topical issues of introducing the evaluation of fiancial instruments and technologies, which is critically important for ensuring the effective functioning of the fiancial market. There is a justifid need to introduce evaluation of fiancial instruments and technologies to ensure economic stability. This allows investors, companies and regulators to receive objective information about the risks and prospects of investments, which contributes to making informed decisions. The factors inflencing the organizational and methodical mechanism of forming the initial information base for evaluating fiancial instruments are analyzed and systematized. A comparison of methods of evaluating fiancial instruments was made. A study of fiancial instruments was conducted and we will compare two companies Element Solutions Inc and Invesco QQQ according to indicators of profiability, subsidence and volatility over the last 5 years. In addition, modern fiancial instruments are often based on complex technologies, which makes it diffilt to analyze and evaluate them using traditional methods. To overcome these challenges, new approaches are needed, including those involving the use of big data, artifiial intelligence and machine learning. This will increase the accuracy of the assessment and reduce the level of uncertainty. Regulators also recognize the importance of evaluating fiancial instruments and technologies to ensure compliance of fiancial markets with established standards and to protect investors. In the conditions of globalization of fiancial markets, cooperation between national regulators becomes even more important, as it allows for the creation of coordinated approaches to the assessment and regulation of new fiancial instruments at the international level. Thus, the assessment of fiancial instruments and technologies is not only an important tool for fiancial risk management, but also a necessary element for ensuring the sustainable development of fiancial markets. Given the rapid development of fiancial technologies and innovations, the need to improve valuation methods is becoming increasingly urgent, which emphasizes the relevance of this issue for the modern economy.
Justification of the need to implement assessment of financial instruments and technologies
Keywords: фінансові інструменти і технології; оцінювання; ризики; ефективність; прозорість; прийняття управлінських рішень; інвестори; fiancial instruments and technologies; evaluation; risks; effiency; transparency; management decision-making; investors